2016
DOI: 10.1001/jamafacial.2015.2365
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Facial Deformity

Abstract: The impact of facial defects on quality of life as perceived by society and the value society places on facial reconstruction are important outcomes measures. OBJECTIVE To measure the health state utility and dollar value of surgically reconstructing facial defects as perceived by society. DESIGN, SETTING, AND PARTICIPANTS A randomized observational study conducted in an academic tertiary referral center using a socioeconomically diverse group of 200 casual observers. MAIN OUTCOMES AND MEASURES Observers viewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Facial appearance defines an individual’s identity, and directly influences emotions and social interactions. (40) Therefore, visible scarring can lead to anxiety, poor self-esteem and a decreased quality of life. (41) While satisfaction with facial appearance after surgery is an important outcome, it is often overlooked in dermatologic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial appearance defines an individual’s identity, and directly influences emotions and social interactions. (40) Therefore, visible scarring can lead to anxiety, poor self-esteem and a decreased quality of life. (41) While satisfaction with facial appearance after surgery is an important outcome, it is often overlooked in dermatologic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…(44) Studies have also demonstrated diminished QOL with scarring and the value of reconstruction of facial defects. (6, 40) Therefore, an instrument that measures facial appearance satisfaction and scar outcome is especially applicable to the skin cancer population.…”
Section: Discussionmentioning
confidence: 99%
“…14 Casual observers perceive individuals with facial defects as having a lower health utility and quality of life, a penalty that is normalized in many cases after reconstruction. 13 Furthermore, members of society are less likely to engage and have a conversation with people with facial defects, a social penalty that improved after reconstructive surgery. 8 Within each of these studies that separated facial defects into categories based on defect size and location before reconstructive surgery, a common theme emerged.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous outcome measures described in the facial plastic and reconstructive surgery literature. These can be organized by method (subjective [8][9][10][11][12][13][14][15][16][17][18] or objective [19][20][21][22][23][24][25] ) and perspective (patient, [16][17][18] surgeon or expert, 15,24,25 or society [8][9][10][11][12][13][14][19][20][21][22][23] ). Each of these 6 classes (subjective patient, objective patient, subjective expert, objective expert, subjective society, and objective society) of outcome metrics has utility in the complex assessment of facial deformities and their reconstruction.…”
mentioning
confidence: 99%
See 1 more Smart Citation